Efforts of McDonald’s Towards Green Environment: Case Study on McDonald’s - Nagarajan, Keshika; Kee, Daisy Mui Hung; Thevarajan, Rueben; Kumaran, Sathiaseelan; Letchumanan, Mugentheran; Aziz, Abdul (International Journal of Tourism and Hospitality in Asia Pasific, 2019)
McDonald's is an American fast food company, founded in 1940 as a restaurant operated by Richard and Maurice McDonald, in San Bernardino, California, United States. McDonald's is the world's largest restaurant chain by revenue, serving over 69 million customers daily in over 100 countries across approximately 36,900 outlets as of 2016. Although McDonald's is best known for its hamburgers, cheeseburgers and french fries, they also feature chicken products, breakfast items, soft drinks, milkshakes, wraps, and desserts. In response to changing consumer tastes and a negative backlash because of the unhealthiness of their food, the company has added to its menu salads, fish, smoothies, and fruit. McDonald’s is one of the first big chains in the U.S. to begin widespread testing of plastic straw alternatives. McDonald’s, which operates 14,000 restaurants in the U.S., has been working to find a more sustainable solution for plastic straws globally. The purpose of this project is to analyse the effort taken by Mcdonald’s globally to reduce plastic usage, specifically plastic bags and straws, to find the flaws in their efforts, to provide suggestions to overcome the flaws, enhance learning in organisational behaviour and by this joint project students can learn other cultures and share their experiences globally. The methods that we are going to use to complete this research are by interviewing which enables face to face discussion, brainstorming by having discussion in group to solve the issues, survey, questionnaire, online research method to get more informations, such as company history company organisation. Based on the research, the efficiency of plastic reduction and the methods focused towards green environment. Based on this project, we can conclude that this project can be a new and effective way and solutions to companies that are having flaws in their management and operation.